(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
This paper presents atwo-wave cross-lagged study (average interval of two years) on time precedencein the relationship between organizational climate and organizationalperformance in 171 branches of a financial services organization in theNetherlands. It is argued that four HRM – induced organizational climatedimensions influence organizational performance. Additionally, it was alsohypothesized that high organizational performance influences the fourorganizational climate dimensions through investments in HR practices andthrough signaling effects. Finally, it was reasoned that possibly bothprocesses are present simultaneously. Results of testing a series of competingmodels in AMOS showed that organizational climate at time point 1 influencedorganizational performance at time point 2 rather than the reverse, or both processesbeing present simultaneously.